Penentuan Kuantitas Kehilangan Darah pada Kasus Perdarahan Obstetri: Tinjauan Pustaka - Winata, I Gde Sastra; ., Leonardo; Candijaya, Gita Sirini; Muliawan, Erlin Purnama; Pratama, I Gede Bayu Adi; Pramana, Bagus Andika (PT Kalbe Farma Tbk., 2025)
Postpartum hemorrhage is a leading cause of maternal death worldwide and remains a serious health concern, particularly in developing countries such as Indonesia. Accurate estimation of blood loss is essential for early detection of emergencies and for implementing rapid and appropriate interventions for patients. This review discusses several methods used to determine the amountof blood loss in obstetric cases, including visual estimation, quantitative measurement, and laboratory evaluation. The visual method is easily applied in primary health facilities but frequently underestimates blood loss due to lighting, fluid mixtures, and the experience of health providers. Quantitative methods, such as weighing blood-soaked materials or collecting blood in calibrated containers, are considered more objective and accurate. Laboratory assessment through hemoglobin concentration, hematocrit levels, and spectrophotometric analysis provides confirmation of clinical estimates. Combining quantitative and laboratory approaches can improve diagnostic accuracy, expedite clinical management, and ultimately reduce maternal morbidity and mortality associated with obstetric hemorrhage.